Development and Assessment of a Quantitative Reverse Transcription-PCR Assay for Simultaneous Measurement of Four Amplicons - Grace, Marcy B; McLeland, Christopher B; Gagliardi, Steven J; Smith, Jeffrey M; Jackson, William E., III; Blakely, William F (Clinical chemistry (Baltimore, Md.), 2003)
Background: High-throughput and forward-deployable biological dosimetry capabilities are required for tactical and medical decisions after radiologic events. We previously reported a quantitative reverse transcription (QRT)-PCR assay for human radiation-responsive gene targets using a whole-blood ex vivo irradiation model, but we needed a multitarget assay on a smaller, less costly, real-time PCR detection system. Methods: We developed a quadruplex QRT-PCR assay in a 96-well, closed-plate format suitable for use with RNA extracted from whole blood. Four cDNA targets were simultaneously amplified in a sealed tube by hybridization to exonuclease probes, each conjugated to distinct fluorogenic reporters. A novel primer-limited 18S rRNA reference target was validated from serial dilutions of human total RNA. To test assay precision, we incorporated a positive-control cDNA mimic into duplex and quadruplex PCR reactions. The master mixture was supplemented with more enzyme, MgCl2, and deoxyribonucleotides. Simultaneous detection of four targets was evaluated in comparison with respective duplex QRT-PCR assays. Results: The simultaneous detection of three radiation-responsive genes by quadruplex QRT-PCR was quantitative, with gene expression changes similar to those observed with optimized duplex and triplex QRT-PCR assays. The 18S rRNA and GADD45 calibration curves (threshold cycle vs log10 cDNA) were linear and reproducible and showed optimal PCR efficiencies as indicated by slopes statistically equivalent to the theoretical value of −3.322. Conclusions: This is the first study of a quadruplex QRT-PCR assay. Our approach has diagnostic utility in the detection of biomarkers, biological and toxicologic agents, and genes of inherited diseases and cancer.